Implementation of Character Education in Learning Quality Through School Culture in Pangkalan Kerinci - Juliana; Zarkasih; Jaka Warsihna (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper investigates the implementation of character education in learning quality through school culture in Pangkalan Kerinci. It is common that more attention should be paid to the moral character of our youth. Such pleas are prevalent in the mass media and in professional forums and are usually justified by data reflecting juvenile delinquency. The research uses a qualitative descriptive approach by involving various stakeholders as participants, including teachers, students, and school administrators. Data were collected through in-depth interviews, observations, and document analysis by focusing on the role of school culture in building character education. The research results indicate that the school culture in Pangkalan Kerinci plays an essential role in building character education and learning quality. The findings reveal that schools in the region implemented values-based pedagogical strategies and extracurricular activities, which encouraged positive student behavior and academic achievement. In addition, the collaboration between school staff and parents is proven essential in reinforcing students' character development. The study highlights the importance of a supportive school culture, which supports and nurtures character education and improves learning outcomes.